Sufi cosmology (Leiden ; Boston)
xii, 413 sayfa
Keywords: “This volume discusses the origin and structure of the universe in mystical Islam (Sufism) with special reference to parallel realms of existence and their interaction. Contributors address Sufi ideas about the fate of human beings in this and future life under three rubrics: (1) cosmogony and eschatology (“where do we come from?” and “where do we go?”); (2) conceptualizations of the world of the here-and-now (“where are we now?”); and (3) visualizations of realms of existence, their hierarchy and mutual relationships (“where are we in relation to other times and places?”)“ --